Posttraumatic Cognitions, Avoidance Coping, Suicide, and Posttraumatic Stress Disorder Among Adolescent Refugees - Ssenyonga, Joseph; Owens, Vicki; Olema, David Kani (Procedia-Social and Behavioral Sciences, 2013)
This cross-sectional survey examined posttraumatic cognitions, avoidance coping, suicide and trauma-related disorders of Congolese adolescent refugees in Nakivale refugee settlement. We interviewed 89 adolescents (aged 18-24 years; 62.9% females) using the Posttraumatic Cognitions Inventory, Coping Response Inventory, MINI suicidality scale and Posttraumatic Stress Diagnostics Survey. Forty-four (49.4%) adolescent satisfied the PTSD diagnostic criteria. Twenty-six adolescents (29.2%) had moderate to high current suicide risk. Significant predictors including negative cognitions about self, emotional discharge, and acceptance or resignation explained 33.6 percent of the variance in PTSD symptom severity. About 50.8 percent of the variance in PTSD was explained by risk factors including age, trauma load, and negative cognitions about self. The findings suggest that for the adolescent refugees, negative appraisal and avoidance coping strategies used subsequent to trauma exposure have implication for current psychological wellbeing. Therefore there is need to provide psychological intervention to address these maladaptive posttraumatic problems
Keywords: Posttraumatic Cognitions; Avoidance Coping; Mental Health; Adolescent Refugee